Дія шуму вакуумного резервуара на динаміку трирівневого лазера з накачуванням когерентним світлом - Gessesse, M. Molla (Publishing house "Academperiodika", 2020)
We have investigated the effects of vacuum reservoir noise on the photon statistics and quadrature squeezing of light generated by a three-level laser pumped by coherent light and coupled to a vacuum reservoir via a single-port mirror. We have found that the effect of the vacuum reservoir noise is to increase the photon number variance and to decrease the quadrature squeezing. However, the vacuum reservoir noise has no effect on the mean photon number.